Dialogue - Nur Farzana Mohammad Arsad (2017)
Furniture is a true cultural artefact, not, as we often imagine, a mere extension of our body. Furniture creates conversations. Conversations we unconsciously omit regularly, in the midst of rushing headlong towards futuristic ideals. Presented in a moment of confrontation, this set of furniture seeks to coexist the dichotomy between traditionalism and modernism. It stimulates a dialogue, theoretically and physically.